The effect of pineapple (ananas comosus) juice on the perineum wound healing process for postpartum mothers - Nurlaela, Sandy; Susilawati, Susilawati; Susianti, Indah (Science Midwifery, 2024)
Perineal laceration is an injury to the perineum that occurs due to spontaneous tissue damage or through an episiotomy. One effort to treat perineal wounds after giving birth is to consume pineapple juice (Ananas comosus) which contains bromelain, an enzyme that has anti-inflammatory properties which can help in the healing process of perineal wounds. The aim of this research is to determine the effect of giving pineapple juice (Ananas Comosus) on the healing process of perineal wounds in postpartum women at TPMB in Pandeglang Regency in 2024. This research uses a quantitative Quasy Experiment method with a One Group Pre-test Post-test design. The sampling technique for this research was total sampling of 35 respondents. The research period was March - May 2024. The results showed that the majority of postpartum mothers experienced poor perineal wounds (74.3%) in the pretest and good wound healing (82.9%) in the posttest. Statistical test with the Wiloxon Sign Rank Test The p-value obtained = 0.000 < 0.05, meaning that there is an effect of giving pineapple juice (Ananas Comosus) on the healing process of perineal wounds in postpartum.